1992
DOI: 10.1016/0305-1978(92)90082-o
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxonomy of Agelas (Porifera: Demospongiae)

Abstract: Chemotaxonomy of the genus AgelasBraekman, J.C.; Stoller, C.; van Soest, R.W.M. Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitimate complaint, the Library will make the material inaccessible and/or remove it from the website. Please Ask the Library: http://uba.uva.nl/en/contact, or a letter to: Library of the University of Amsterdam, Secretari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0
6

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 88 publications
2
77
0
6
Order By: Relevance
“…If such a deterrent comprises, beside its unpalatability to the fish, any pharmacological potency was only known in part for oroidin. Oroidin is also present within the tissues of A. clathrodes, A. cervicornis, A. dispar and A. wiedenmayeri (Braekman et al, 1992;Assmann et al, 1999Assmann et al, , 2000Lindel et al, 2000;Assmann et al, in press) and has previously been shown to be cytotoxic (König et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If such a deterrent comprises, beside its unpalatability to the fish, any pharmacological potency was only known in part for oroidin. Oroidin is also present within the tissues of A. clathrodes, A. cervicornis, A. dispar and A. wiedenmayeri (Braekman et al, 1992;Assmann et al, 1999Assmann et al, , 2000Lindel et al, 2000;Assmann et al, in press) and has previously been shown to be cytotoxic (König et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Especially sponges are known to be a rich font for interesting secondary metabolites, for example the genus Agelas (Agelasidae) is well known to contain a variety of bromopyrrole alkaloids (reviewed in Braekman et al, 1992;Lindel et al, 2000). Recently, detailed studies have shown both at laboratory and field conditions, that brominated pyrrole alkaloids like 4,5-dibromopyrrole-2-carboxylic acid were the principal fish antifeedant metabolites within the sponge tissue of Agelas sponges at natural concentrations (Pawlik et al, 1995;Chanas et al, 1996;Assmann et al, 2000Assmann et al, , 2004.…”
Section: Introductionmentioning
confidence: 99%
“…As esponjas marinhas foram objeto de intensos estudos no que se refere à sua composição química e bioquímica, com vistas à utilização de metabólitos primários ou secundários como marcadores quimiotaxonômicos [17][18][19] . Isso se deve principalmente à escassez de caracteres anatômicos de fácil observação por métodos convencionais (microscopia óptica) em boa parte das espécies de Porifera, mas também devido à plasticidade morfológica de muitos destes caracteres e à inexistência, até recentemente, de métodos objetivos para o reconhecimento de determinados grupos de esponjas 8,[107][108][109] .…”
Section: Biossíntese E Quimiotaxonomiaunclassified
“…Considera-se que as esponjas foram os primeiros animais marinhos estudados do ponto de vista químico [11][12][13][14][15][16] . Estudos com produtos naturais de esponjas marinhas forneceram importantes informações do ponto de vista quimiotaxonômico [17][18][19][20] , ecológi-co [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] . Sem perder tempo, ele as corta vigorosamente com uma pequena foice.…”
Section: Introductionunclassified
See 1 more Smart Citation